Self-rated health of both US citizens and noncitizens is associated with state-level immigrant criminalization policies - Maria-Elena De Trinidad Young; Danielle M. Crookes; Jacqueline M. Torres (Elsevier, 2022)
Evidence shows that state-level restrictive immigrant policies are associated with health disparities between noncitizens and citizens. Most research has focused on Latinos and there is limited knowledge of the relationship between restrictive policies and citizenship status among other groups, particularly Asian and Pacific Islanders (API). We examined whether state-level criminalization policy contexts (e.g., law enforcement collaboration with immigration authorities, E-Verify employment authorization) were associated with self-rated health (SRH) by citizenship, with a focus on Latinos and APIs. We expected that criminalization policies would be associated with worse health for noncitizens and citizens, but with a more negative influence for noncitizens; and that this pattern would be the same for Latinos and APIs. We merged a state-level immigrant criminalization policy database with a multi-racial/ethnic sample from 2014 to 2015 National Health Interview Survey (NHIS, n = 70,335). We tested the association between SRH and the number of state-level criminalization policies and generated predicted probabilities of noncitizens and citizens reporting excellent health in states with the most and fewest criminalization policies for the full sample, Latino, and API respondents. In states with the most criminalization policies, all noncitizens had a higher and all US-born citizens had a lower probability of excellent health. In states with the fewest criminalization policies there were no differences by citizenship status. Findings provide new evidence that state-level immigrant policies may harm the health of US-born citizens. As immigrant policymaking at the state level continues, understanding the relationship between state-level immigrant policies and health inequities across citizenship statuses will continue to be critical to improving population health.